Electron transport layer and preparation method and application thereof

By growing graphyne in situ on the surface of the SnO2 electron transport layer, and using hexaethynylbenzene precursor molecules to target oxygen vacancies, the problem of oxygen vacancies on the surface of SnO2 affecting the performance of perovskite solar cells is solved, and the interface properties are optimized and cell performance is improved.

CN119546043AActive Publication Date: 2025-02-28SHANDONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411621565.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The presence of oxygen vacancy on the surface of SnO2 leads to the limitation of the photoelectric properties and crystal growth of perovskite solar cells, and the existing interface modification methods are uncontrollable.

Method used

Graphene is grown in situ on the surface of the SnO2 electron transport layer through Glaser-Hay coupling reaction, and targeted oxygen vacancies using hexaethynylbenzene precursor molecules to achieve targeted passivation of oxygen vacancies on the surface of SnO2.

Benefits of technology

The oxygen vacancies on the surface of SnO2 were effectively managed, the interface properties between SnO2 and the perovskite layer were optimized, and the photoelectric conversion efficiency and stability of perovskite solar cells were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546043A_ABST
    Figure CN119546043A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cells, and particularly relates to a graphdiyne (GDY) in-situ growth electron transport layer (ETL), a preparation method thereof and application of the electron transport layer in targeted management of tin oxide (SnO2) surface oxygen vacancies in a solar cell. And the electron transport layer is a SnO2 film with a graphdiyne passivation layer grown in situ on the surface. And assembling a solar cell by using the obtained electron transport layer, wherein the solar cell comprises a transparent conductive substrate, the electron transport layer, a perovskite active layer, a perovskite modification layer, a hole transport layer and a metal counter electrode which are sequentially arranged from bottom to top. According to the method, the oxygen vacancy defect on the surface of SnO2 is efficiently passivated, so that non-radiative recombination is effectively inhibited, meanwhile, the interface energy level matching degree is optimized, and the charge extraction and transmission capacity is remarkably improved; meanwhile, effective adjustment of interface performance and chemical environment between SnO2 and perovskite is realized through defect management of graphdiyne, and optimization of perovskite crystal quality is realized synergistically. The preparation method provided by the invention is simple and easy to realize, has high repeatability, and effectively improves the photoelectric conversion efficiency and stability of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to a graphyne in-situ grown electron transport layer and a preparation method thereof, and an application of the graphyne in-situ grown electron transport layer in targeted management of oxygen vacancies on the surface of tin oxide in solar cells. Background Art

[0002] Due to their excellent optoelectronic properties, organic-inorganic halide perovskite materials have attracted much attention in next-generation photovoltaic devices and show bright application prospects. In recent years, the photoelectric conversion efficiency (PCE) of perovskite solar cells (PSCs) has rapidly increased from 3.8% to 26.5%. Among them, SnO2, as an efficient electron transport layer, has played a key role in the latest breakthroughs in the photoelectric conversion efficiency of the corresponding devices and has shown great development potential. Although SnO2 has unique advantages (such as good energy level arrangement, high transmittance, high electron mobility, and easy processing at low temperatures), a large number of defects are still inevitably formed on the SnO2 surface during film preparation and solution spin coating. There are mainly three types of defects on the SnO2 surface: oxygen vacancies (Vo), unsaturated Sn dangling bonds, and basic terminal -OH bound to one Sn site and acid bridge -OH bound to two Sn sites.

[0003] The presence of oxygen vacancies reflects the non-stoichiometry of SnO2 films, which means the presence of Sn dangling bonds with different oxidation states on the surface, which greatly affects the chemical environment and optoelectronic properties at the SnO2 / perovskite (PVSK) interface, thereby limiting the charge transfer performance at the interface and the crystal growth of the upper perovskite. At the same time, oxygen vacancies on the SnO2 surface will also significantly affect the electrical and chemical properties of the SnO2 ETL itself. Because the two electron-donating energy levels of oxygen vacancies are below the minimum of the SnO2 ETL conduction band, they can strongly affect the electron concentration associated with these two electron-donating energy levels. Therefore, the conductivity of the SnO2 ETL is closely related to the number of oxygen vacancies. In addition, oxygen vacancies usually have positive charge centers, which easily act as electron capture traps and form barriers that hinder electron transfer. Therefore, the carrier concentration is directly related to the interfacial non-radiative recombination caused by oxygen vacancies. To date, many effective surface modification strategies and interface engineering techniques have been reported in the literature to improve the interfacial energy level arrangement and suppress carrier recombination. Ionic salts or functionalized organic molecules are often used as interface modifiers to passivate defects on the SnO2 surface. However, these passivating molecules are usually added by spin coating, and their interaction sites with SnO2 surface defects are random, which can lead to uncontrollable regulation and modification of the interface environment. Therefore, achieving in-situ introduction of passivating agents is an important way to overcome this huge challenge. Summary of the invention

[0004] The present invention aims to provide a graphyne in-situ grown electron transport layer and a preparation method thereof, and an application of the graphyne in-situ grown electron transport layer in targeted management of oxygen vacancies on the surface of tin oxide in solar cells.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] An electron transport layer is a SnO2 film with a graphyne passivation layer grown in situ on the surface.

[0007] A method for preparing the electron transport layer is to achieve in-situ growth of graphyne on the surface of SnO2ETL through a Glaser-Hay coupling reaction so that graphyne forms an interface passivation layer with the surface.

[0008] Furthermore, a substrate with a SnO2 film is added to a reaction vessel, and cuprous iodide, acetone, pyridine and N,N,N',N'-tetramethylethylenediamine are added in sequence, and then the precursor solution is added to the system. After mixing, the reactor is placed in an argon atmosphere at 50-60°C to react in the dark (to avoid light irradiation to induce the reaction). After the reaction, the SnO2 film with an in-situ grown graphyne passivation layer on the surface is obtained by washing.

[0009] The precursor solution is a hexaethynylbenzene (HEB) precursor molecule dissolved in acetone (the concentration is controlled at 0.13-0.67 mg / ml); the amount of the catalyst cuprous iodide in the reaction system is 0.005-0.013 mmol, and the volume ratio of acetone, pyridine and N,N,N',N'-tetramethylethylenediamine is 100:1:1-100:1:10.

[0010] The substrate with the SnO2 thin film is obtained by spin coating a SnO2 precursor solution on the substrate.

[0011] The SnO2 film is prepared by diluting a SnO2 colloid solution (15% aqueous colloid dispersion) with ultrapure water to obtain SnO2:H2O=1:3-1:5 (v:v), ultrasonically dispersing for 15-30 minutes to obtain a SnO2 precursor solution; then spin coating the solution on a homogenizer at a speed of 3000-4000 rpm for 30-40 seconds, annealing at 150°C for 15-30 minutes, and cooling the solution to room temperature for later use.

[0012] An application of the electron transport layer, the application of the electron transport layer in the preparation of organic-inorganic halide perovskite solar cells.

[0013] An organic-inorganic halide perovskite solar cell comprises a transparent conductive substrate, an electron transport layer, a perovskite active layer, a perovskite modification layer, a hole transport layer and a metal counter electrode arranged in sequence from bottom to top, wherein the electron transport layer is a SnO2 film with a graphyne passivation layer in situ grown on the surface.

[0014] Furthermore, on the SnO2 ETL surface, oxygen vacancies on the tin oxide surface in solar cells were targeted and managed through in situ growth of pyrimidine, and an interface passivation channel was successfully constructed.

[0015] The in-situ growth of graphyne is achieved by Glaser-Hay coupling reaction on the surface of SnO2 ETL. Hexaethynylbenzene (HEB) precursor molecules are dissolved in acetone as a precursor solution, and cuprous iodide, acetone, pyridine and N,N,N',N'-tetramethylethylenediamine are added in sequence to a reaction bottle containing copper foil and FTO (SnO2), and the precursor solution is slowly added dropwise. The reaction is carried out in an argon atmosphere at 60°C in the dark. Due to the strong electronic interaction between the acetylenic bond and the oxygen vacancy, the hexaethynylbenzene (HEB) precursor molecule can be targeted and anchored on the oxygen vacancy on the SnO2 surface. With the cross-coupling of the precursor molecules, graphyne can be directly grown in-situ on the SnO2 film, and the in-situ growth process is monitored according to different reaction times. After the reaction, it was washed several times with deionized water, N,N-dimethylformamide (DMF) and acetone, and finally an in-situ grown graphyne passivation layer (FTO / SnO2 / GDY) was successfully obtained on the SnO2 film.

[0016] A method for preparing an organic-inorganic halide perovskite solar cell: forming a SnO2 electron transport layer on the surface of a substrate, forming an in-situ grown graphyne passivation layer on the surface of the transport layer as described above; and then modifying the perovskite precursor solution on the surface of the layer by spin coating deposition to obtain a perovskite active layer film;

[0017] Further, a solution containing phenylethylammonium iodide (PEAI) is spin-coated on the surface of the perovskite active layer film formed above to form a perovskite modification layer on the surface of the perovskite active layer film; after formation, the hole transport layer is modified by spin coating, aged, and a metal counter electrode is prepared after the treatment to obtain a solar cell.

[0018] The perovskite precursor solution is prepared by weighing 912.8 mg PbI2 (1.98 M), 309.6 mg FAI (1.8 M), 42.5 mg MACl (0.63 M) and 57.4 mg CsPbBr3 (0.1 M), mixing them in 1000 μL of a mixed solvent (DMF:DMSO=4:1, v:v), and continuously shaking them on a vortex oscillator for 2 h to fully dissolve and mix them to obtain a perovskite precursor solution.

[0019] The Spiro-OMeTAD precursor solution uses chlorobenzene as a solvent, and each 1000 μL of the solvent contains 80-100 mg of Spiro-OMeTAD powder, 25-30 μL of tetra-tert-butylpyridine solution, 10-20 μL of acetonitrile solution containing lithium bis-trifluoromethanesulfonyl imide, and 10-20 μL of acetonitrile solution containing FK209 Co(III)TFSI. The concentration of lithium bis-trifluoromethanesulfonyl imide in the acetonitrile solution is 520 mg / mL, and the concentration of FK209 Co(III)TFSI is 350 mg / mL.

[0020] Specifically:

[0021] Step (1) A commercially purchased etched FTO glass substrate was ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15 min respectively, then dried with nitrogen, and then plasma treated for 15 min;

[0022] Step (2): dilute the SnO2 solution (15% aqueous colloidal dispersion) with ultrapure water, spin-coat it on the substrate surface at a rotation speed of 3700 rpm for 30 seconds, and then anneal it on a hot plate at 150° C. for 15 minutes to prepare a SnO2 electron transport layer;

[0023] Step (3): The pretreated FTO conductive glass sheet with SnO2 film is placed in a three-necked reaction bottle for storage. Then, the GDY monomer hexa(trimethylsilylethynyl)benzene (HEB-TMS) is added to a 100 mL reaction bottle for deprotection reaction, dissolved with tetrahydrofuran, and tetrabutylammonium fluoride is added at the same time. Stirring is continued for 10 minutes, and the temperature is always kept below zero during this process. It is then extracted with ethyl acetate and saturated brine, and the resulting solution is dried with anhydrous Na2SO4. The solvent is then removed in a vacuum rotary evaporator to obtain the graphene precursor HEB, and HEB is dissolved in acetone as a precursor solution. Next, cuprous iodide, acetone, pyridine and N,N,N',N'-tetramethylethylenediamine are added to the reaction bottle containing FTO (SnO2) in sequence, and the precursor solution is slowly added dropwise. The reaction was carried out in an argon atmosphere at 60°C in the dark, and GDY could be directly grown in situ on the SnO2 film. The in situ growth process was monitored according to different reaction times. After the reaction, it was washed with deionized water, DMF and acetone several times, and finally an in situ grown GDY passivation layer (FTO / SnO2 / GDY) was successfully obtained on the SnO2 film.

[0024] Step (4): The perovskite precursor solution is deposited by spin coating, which is divided into two steps. The first step is 1000 rpm, lasts for 10 seconds, and the acceleration per second is 1000 rapm; the second step is 5000 rpm, lasts for 30 seconds, and the acceleration per second is 1000 rapm. 15 seconds before the end of spin coating, 200 μL of ethyl acetate is added for anti-solvent treatment to form a film of the perovskite precursor solution, and then annealed at 100°C for 50 minutes in a glove box to obtain a perovskite active layer film;

[0025] Step (5): using isopropanol as solvent to prepare a 2 mg / ml phenylethylammonium iodide (PEAI) solution, and spin coating the solution on the perovskite active layer at 4000 rpm for 20 seconds to obtain a perovskite modified layer;

[0026] Step (6): Spin-coat the Spiro-OMeTAD solution on the prepared perovskite active layer at a speed of 4000 rpm for 30 seconds to obtain a hole transport layer, and transfer the solution to an electronic moisture-proof box with a fixed humidity and age it in an air atmosphere for about 15 hours;

[0027] Step (7): Place the aged perovskite device into a mask with suitable specifications and use a vacuum coating machine to coat the perovskite device with a thickness of at least 1×10 -7 Pa under high vacuum conditions. By evaporating a 100nm silver electrode at a rate of , the prepared perovskite solar cell can be obtained.

[0028] Working principle:

[0029] The present invention achieves targeted passivation of SnO2 surface defects by controlling the in-situ growth of graphyne on the surface of SnO2 ETL. The highly active hexaethynylbenzene precursor molecule is first anchored on the oxygen vacancies of SnO2. As the cross-coupling of the precursor molecules proceeds, effective electron transfer occurs between graphyne and SnO2, and the interaction between the acetylene bond and SnO2 induces ene-acetylene interconversion, which is beneficial to increase the overall chemical valence state of the surface tin atoms and reduce the oxygen vacancy trap state. In addition, the in-situ growth of graphyne can optimize the surface morphology of tin oxide, regulate the electrical properties and chemical contact at the interface between tin oxide and perovskite, and improve the crystallinity and vertical growth orientation of the upper perovskite. This invention achieves precise management of electronic layer defects and regulation of interface properties, which significantly optimizes the performance of perovskite solar cell devices.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) Based on the property that graphyne can be controllably grown in situ on any substrate surface, this paper proposes a new strategy for in situ growth of graphyne on the SnO2 ETL surface and successfully constructs an interface passivation channel.

[0032] (2) The present invention utilizes the hexaethynylbenzene precursor molecule to be targeted and anchored on the oxygen vacancies on the SnO2 surface, thereby achieving the in-situ growth of graphyne on the SnO2 surface, thereby effectively managing the SnO 2 Surface oxygen vacancies.

[0033] (3) The present invention ensures the property regulation of the interface between SnO2 and the perovskite layer through in-situ growth and defect management of graphyne, and synergistically achieves the optimization of the crystallinity of the perovskite layer, which is conducive to the preparation of high-performance and high-stability perovskite solar cells. At the same time, the present invention has a low production cost and a simple preparation method, which is more conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A schematic diagram of the in-situ growth of graphyne for targeted management of oxygen vacancies on the surface of tin oxide in a solar cell according to the present invention;

[0035] Figure 2 The SEM and AFM images of the SnO2 control film and graphyne in-situ grown on the SnO2 ETL surface of the present invention;

[0036] Figure 3 FT-IR spectrum of the interaction between SnO2 and graphyne in the present invention;

[0037] Figure 4 The XPS images of the SnO2 control film and graphyne in-situ grown on the SnO2 ETL surface of the present invention;

[0038] Figure 5 The dark IV curves and electron mobility of the SnO2 control film and graphyne grown in situ on the SnO2 ETL surface of the present invention;

[0039] Figure 6 The SEM images of the control perovskite film and the graphyne-treated perovskite film of the present invention;

[0040] Figure 7 GIWAXS images of control perovskite film and graphyne treated perovskite film;

[0041] Figure 8 PL and TRPL spectra of the control and graphyne-treated perovskite films of the present invention;

[0042] Fig. 9 It is a schematic diagram of the energy level arrangement of the present invention;

[0043] Fig.10 Schematic diagram of the structure of the perovskite device and the PCE distribution histogram of the present invention;

[0044] Fig.11 JV curves of forward and reverse scans of the control device and the Graphene Oxide-treated device of the present invention;

[0045] Fig.12 The long-term stability test curves of the unpackaged control device and the graphyne treated device of the present invention in N2 atmosphere. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, but these embodiments do not limit the scope of the present invention.

[0047] The present invention manages the oxygen vacancies on the SnO2 surface in the solar cell through the in-situ growth of graphyne, thereby improving the performance and stability of the cell. The structure of the perovskite solar cell is: a transparent conductive substrate, an electron transport layer, a SnO2 modified layer, a perovskite active layer, a hole transport layer and a metal counter electrode. Among them, the transparent conductive substrate uses FTO, the electron transport layer is prepared by spin coating with SnO2 colloidal aqueous solution, the interface of the SnO2 electron transport layer / perovskite light absorption layer is modified with graphyne to construct a targeted passivation layer, the perovskite light absorption layer is prepared with organic and inorganic halide perovskites, the hole transport layer is prepared with Spiro-OMeTAD, and the metal Ag electrode is used as the counter electrode.

[0048] In the following examples, the SnO2 precursor solution is prepared by diluting the SnO2 colloidal solution (15% aqueous colloidal dispersion) with ultrapure water to obtain SnO2:H2O=1:3 (v:v), and ultrasonically dispersing for 15 minutes to obtain the SnO2 precursor solution. Then, the solution is spin-coated onto the FTO substrate on a homogenizer at a speed of 3700 rpm for 30 seconds, and annealed at 150°C for 30 minutes. After cooling to room temperature, the solution is transferred to a three-necked reaction bottle filled with an argon atmosphere for in-situ growth reaction of graphyne.

[0049] Example 1

[0050] like Figure 1 A schematic diagram of the in-situ growth of GDY on the surface of SnO2 film and the targeted passivation of oxygen vacancies on the SnO2 surface is shown.

[0051] Step (1) A commercially purchased etched FTO glass substrate was ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15 min respectively, then dried with nitrogen, and then plasma treated for 15 min;

[0052] Step (2): dilute the SnO2 solution (15% aqueous colloidal dispersion) with ultrapure water, spin-coat it on the substrate surface at a rotation speed of 3700 rpm for 30 seconds, and then anneal it on a hot plate at 150° C. for 15 minutes to prepare a SnO2 electron transport layer;

[0053] Step (3): The pretreated FTO conductive glass sheet with SnO2 film is placed in a three-necked reaction bottle for storage. Then 10 mg of GDY monomer hexa(trimethylsilylethynyl)benzene (HEB-TMS) is added to a 100 mL reaction bottle for deprotection reaction, dissolved with 20 mL of tetrahydrofuran, and 0.3 mL of tetrabutylammonium fluoride is added at the same time. Stirring is continued for 10 min, and the temperature is always kept below zero during this process. Then, extraction is performed with an appropriate amount of ethyl acetate and saturated brine, and the resulting solution is dried with anhydrous Na2SO4. Then, the solvent is removed in a vacuum rotary evaporator to obtain the graphene precursor HEB, and HEB is dissolved in 30 mL of acetone as a precursor solution. Next, 1 mg of cuprous iodide, 100 mL of acetone, 1 mL of pyridine and 10 mL of N,N,N',N'-tetramethylethylenediamine are added to the reaction bottle containing FTO (SnO2) in sequence, and the precursor solution is slowly added dropwise. The reaction was carried out in an argon atmosphere at 60°C in the dark, and GDY could be directly grown in situ on the SnO2 film. The reaction time was controlled to be 1 hour, and the in situ growth process was monitored. After the reaction, it was washed with deionized water, DMF and acetone several times, and finally an in situ grown GDY passivation layer (FTO / SnO2 / GDY) was successfully obtained on the SnO2 film.

[0054] Step (4): The perovskite precursor solution (912.8 mg PbI2 (1.98 M), 309.6 mg FAI (1.8 M), 42.5 mg MACl (0.63 M) and 57.4 mg CsPbBr3 (0.1 M) mixed in 1000 μL mixed solvent (DMF:DMSO = 4:1, v:v)) was deposited by spin coating, with a two-step spin coating procedure. The first step was a spin coating speed of 1000 rpm, a duration of 10 s, and an acceleration of 1000 rapm per second; the second step was a spin coating speed of 5000 rpm, a duration of 30 s, and an acceleration of 1000 rapm per second. 15 s before the end of the spin coating, 200 μL of ethyl acetate was added for anti-solvent treatment to form a film of the perovskite precursor solution, and then annealed at 100 ° C for 50 min in a glove box to obtain a perovskite active layer film;

[0055] Step (5): using isopropanol as solvent to prepare a 2 mg / ml phenylethylammonium iodide (PEAI) solution, and spin coating the solution on the perovskite active layer at 4000 rpm for 20 seconds to obtain a perovskite modified layer;

[0056] Step (6): Spin-coat the Spiro-OMeTAD solution on the prepared perovskite active layer at a speed of 4000 rpm for 30 seconds to obtain a hole transport layer, and transfer the solution to an electronic moisture-proof box with a fixed humidity and age it in an air atmosphere for about 15 hours;

[0057] Step (7): Place the aged perovskite film into a mask with suitable specifications and use a vacuum coating machine to coat the film at a depth of at least 1×10 -7 Under the high vacuum conditions of Pa, MoO3 and Ag are deposited on the upper surface of the hole transport layer by thermal evaporation to obtain the prepared perovskite solar cell.

[0058] Control group 1

[0059] Step (1) A commercially purchased etched FTO glass substrate was ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15 min respectively, then dried with nitrogen, and then plasma treated for 15 min;

[0060] Step (2): dilute the SnO2 solution (15% aqueous colloidal dispersion) with ultrapure water, spin-coat it on the substrate surface at a rotation speed of 3700 rpm for 30 seconds, and then anneal it on a hot plate at 150° C. for 15 minutes to prepare a SnO2 electron transport layer;

[0061] Step (3): The perovskite precursor solution (912.8mg PbI2 (1.98M), 309.6mg FAI (1.8M), 42.5mg MACl (0.63M) and 57.4mg CsPbBr3 (0.1M) mixed in 1000μL mixed solvent (DMF:DMSO = 4:1, v:v)) was deposited by spin coating, with a two-step spin coating procedure. The first step was a spin coating speed of 1000rpm, a duration of 10s, and an acceleration of 1000rapm per second; the second step was a spin coating speed of 5000rpm, a duration of 30s, and an acceleration of 1000rapm per second. 15s before the end of the spin coating, 200μL of ethyl acetate was added for anti-solvent treatment to form a film of the perovskite precursor solution, and then annealed at 100°C in a glove box for 50min to obtain a perovskite active layer film;

[0062] Step (4): using isopropanol as solvent to prepare a 2 mg / ml phenethylammonium iodide (PEAI) solution, and spin coating the solution on the perovskite active layer at 4000 rpm for 20 seconds to obtain a perovskite modified layer;

[0063] Step (5): Spin-coat the Spiro-OMeTAD solution on the prepared perovskite active layer at a speed of 4000 rpm for 30 seconds to obtain a hole transport layer, and transfer the solution to an electronic moisture-proof box with a fixed humidity and age it in air atmosphere for about 15 hours;

[0064] Step (6): Place the aged perovskite film into a mask with suitable specifications and use a vacuum coating machine to coat the film at a depth of at least 1×10 -7 Under the high vacuum conditions of Pa, MoO3 and Ag are deposited on the upper surface of the hole transport layer by thermal evaporation to obtain the prepared perovskite solar cell.

[0065] Step (7): Perform performance testing using the above examples and control examples.

[0066] Depend on Figure 2 Scanning electron microscopy (SEM) images show that before the in-situ growth of GDY, the SnO2ETL presents an uneven film state on the FTO surface, and pinhole-like pores can be clearly observed. The GDY film grows evenly on the SnO2 surface and tends to be in the uneven area of ​​the surface, indicating that the in-situ growth of GDY successfully achieves the pinhole filling and surface flatness optimization of the SnO2 film. The morphology of the in-situ growth of GDY on the surface of the SnO2 film was further explored by atomic force microscopy (AFM). The GDY film is evenly distributed on the SnO2 surface, which is consistent with the SEM results, further confirming the effective realization of the in-situ growth of GDY. More importantly, compared with the surface roughness of the original SnO2 film of 1.57nm, the roughness value of the SnO2 film after GDY passivation is significantly reduced to 0.84nm, which will be beneficial to the spreading of the perovskite precursor solution and the nucleation and growth of perovskite.

[0067] During the growth process of GDY, we first tracked the intermolecular interactions between GDY and SnO2 by Fourier transform infrared spectroscopy (FT-IR), such as Figure 3 As shown: In SnO2 / HEB, at 3090cm -1 An obvious stretching vibration characteristic peak of olefinic hydrogen (=CH) appears at 948cm. This is because the strong electronic interaction between HEB and SnO2 causes part of the charge of HEB to be transferred to SnO2, which in turn causes part of the acetylenic bond to break and transform into olefinic bonds. After the in-situ growth of GDY is completed, the interaction between it and SnO2 is further tracked by infrared spectroscopy. Compared with pure GDY, the infrared results of SnO2 / GDY show that the peak at 948cm -1 A new chemical bond C-O appears at 500 cm-1, indicating that the acetylene bond C in GDY forms a covalent bond with the O in SnO2. -1The nearby O-Sn-O bond also underwent a significant blue shift. The above results all indicate that the existence of the alkyne bond leads to a strong electronic interaction between GDY and SnO2, and the alkyne bond C can target and bind to the O atom on SnO2, resulting in charge transfer between molecules.

[0068] The interaction between GDY and SnO2 and the effect of GDY on oxygen vacancy management were further investigated by X-ray photoelectron spectroscopy (XPS). Figure 4 As shown, the C1s spectrum of the original GDY shows that at 284.4 eV (sp 2 There are four sub-peaks at 284.9eV (sp-C), 286.2eV (CO) and 288.4eV (C=O). In the C1s spectrum of SnO2 / GDY film, there are four sub-peaks at 284.5eV (sp 2 Five peaks were detected at 285.0eV (sp-C), 286.3eV (CO), 288.2eV (C=O) and 289.4eV (π-π* transition). The π-π* transition peak at 289.4eV means the existence of delocalized π electrons, revealing the electronic interaction between GDY and SnO2. Especially for the original GDY structure, I sp-C / sp2-C =2. When GDY is introduced in situ onto the SnO2 surface, I sp-C with I sp2-C The ratio of GDY to SnO2 decreased to 1.86, indicating that some alkyne bonds were broken by intermolecular interactions, which is consistent with the infrared results. In order to further study the effect of GDY on the passivation of oxygen vacancies on the SnO2 surface, the Sn3d and O1s XPS fine spectra were analyzed in detail. With the introduction of GDY, the Sn 3d spectrum moved 0.32 eV to high binding energy. 5 / 2 The XPS spectrum was analyzed in detail and it was found that the I Sn4+ / I Sn2+ The ratio is 2.05, while in SnO2 / GDY film this ratio is significantly increased to 7.69. This result shows that the electron transfer between SnO2 and the acetylene bond induces the change of the chemical valence state of the nearby Sn, and the coordination-unsaturated Sn 2+ Effectively converted to Sn 4+ , thereby significantly reducing the concentration of oxygen vacancies. In addition, the XPS spectrum of O 1s contains three peaks, and the binding energies correspond to lattice oxygen (O lattice ), vacancy oxygen (O vacancy ) and chemically adsorbed oxygen (O chemical ). As GDY is passivated, the lattice oxygen (O-Sn 4+ ) signal intensity increased significantly, and the signal intensity of vacancy oxygen decreased significantly (O-Sn 2+ It is worth mentioning that lattice oxygen and vacancy oxygen (IO 2- / IO vacancy ) This ratio is 1.77 in pristine SnO2 and significantly increases to 2.72 after in-situ passivation with GDY, indicating that oxygen vacancies are well suppressed due to the strong electronic interaction between GDY and SnO2.

[0069] like Figure 5 As shown in Figure 2, a pure electronic device with glass / FTO / ETL / Al structure was constructed, and the conductivity and electron mobility of SnO2 and SnO2 / GDY ETL were tested by space charge limited current method (SCLC). After GDY in situ growth, the electron mobility increased from 1.56×10 -4 cm 2 ·V -1 ·s -1 Increased to 4.40×10 -4 cm 2 ·V -1 ·s -1 Meanwhile, the dark IV curves recorded under light-shielded conditions show that the conductivity of the SnO2 / GDY-based ETL increases significantly. The above results indicate that GDY significantly optimizes the charge extraction and transport at the SnO2 interface, which is due to the effective suppression of oxygen vacancies on the SnO2 surface, which enhances its electrical properties.

[0070] Figure 6 SEM images of perovskite films deposited on SnO2 without GDY passivation and after GDY in-situ passivation are shown. Compared with the original perovskite film, the SnO2 / GDY-based perovskite film is flatter and has a more uniform grain size. The average grain size of the original perovskite film is about 1.15μm, while the average grain size of the SnO2 / GDY-based perovskite film increases to 1.22μm.

[0071] The influence of SnO2 surface properties on the orientation and crystallinity of the upper perovskite crystals was studied by grazing incidence wide-angle X-ray scattering (GIWAXS) test. Figure 7 As shown, SnO2-based and SnO2 / GDY-based perovskite films at q = 10nm -1 The peak intensity of the α-phase signal of the perovskite film based on the GDY-optimized substrate is significantly increased. z The GDY passivation layer has a higher intensity in the SnO2 / perovskite direction, which indicates that the GDY passivation layer has a better interface property, making the perovskite crystals more inclined to grow in a vertical orientation. Therefore, the GDY in-situ passivation provides an optimized interface environment for the crystallization and growth of perovskite films, and will also be beneficial to the charge extraction and transport at the SnO2 / perovskite interface.

[0072] Steady-state fluorescence (PL) and transient fluorescence (TRPL) tests were performed to study the effect of GDY passivation on the interfacial charge transfer dynamics. The results showed that the charge extraction and transfer process of FTO / SnO2 / GDY / perovskite film was faster (see Figure 8 ).

[0073] Ultraviolet photoelectron spectroscopy (UPS) analysis revealed that the construction of the graphyne passivation layer can optimize the device energy level arrangement and promote the transport of carriers (see Fig. 9 ).

[0074] The device performance was further tested by spin-coating an electron transport layer, a GDY in-situ grown passivation layer, a perovskite active layer, a perovskite modification layer, a hole transport layer, and a vapor-deposited metal counter electrode on a transparent conductive substrate layer by layer to form a perovskite battery device, and the device performance and stability were tested under simulated sunlight.

[0075] Depend on Fig.10 and Fig.11 It can be seen that the effective passivation of oxygen vacancies on the SnO2 surface by in-situ growth of GDY can significantly reduce the device hysteresis effect, and the average photoelectric conversion efficiency is increased from 23.01% of the reference device to 24.78%; and compared with the control device, the long-term stability of the GDY-based device is significantly improved ( Fig.12 ).

[0076] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An electron transport layer, characterized in that: The electron transport layer is a SnO2 film with a graphyne passivation layer grown in situ on the surface.

2. A method for preparing an electron transport layer according to claim 1, characterized in that: The in-situ growth of graphyne is achieved on the surface of the tin oxide electron transport layer through a Glaser-Hay coupling reaction, so that an interface passivation layer is formed between the graphyne and the surface.

3. The method for preparing an electron transport layer according to claim 2, characterized in that: The substrate with SnO2 film is added to the reaction container, and cuprous iodide, acetone, pyridine and N,N,N',N'-tetramethylethylenediamine are added in sequence, and then the precursor solution is added to the system. After mixing, the reactor is placed in an argon atmosphere at 50-60°C and protected from light for reaction (to avoid light irradiation to induce the reaction). After the reaction, the SnO2 film with an in-situ grown graphyne passivation layer on the surface is obtained by washing.

4. The method for preparing an electron transport layer according to claim 2, characterized in that: The precursor solution is a hexaethynylbenzene (HEB) precursor molecule dissolved in acetone (the concentration is controlled at 0.13-0.67 mg / ml); the amount of the catalyst cuprous iodide in the reaction system is 0.005-0.013 mmol, and the volume ratio of acetone, pyridine and N,N,N',N'-tetramethylethylenediamine is 100:1:1-100:1:

10.

5. The method for preparing an electron transport layer according to claim 2, characterized in that: The substrate with the SnO2 thin film is obtained by spin coating a SnO2 precursor solution on the substrate.

6. The method for preparing an electron transport layer according to claim 5, characterized in that: The SnO2 film is prepared by diluting a SnO2 colloid solution (15% aqueous colloid dispersion) with ultrapure water to obtain SnO2:H2O=1:3-1:5 (v:v), ultrasonically dispersing for 15-30 minutes to obtain a SnO2 precursor solution; then spin coating the solution on a homogenizer at a speed of 3000-4000 rpm for 30-40 seconds, annealing at 150°C for 15-30 minutes, and cooling the solution to room temperature for later use.

7. An application of the electron transport layer according to claim 1, characterized in that: Application of the electron transport layer in preparing organic and inorganic halide perovskite solar cells.

8. An organic-inorganic halide perovskite solar cell, the solar cell comprising a transparent conductive substrate, an electron transport layer, a perovskite active layer, a perovskite modification layer, a hole transport layer and a metal counter electrode arranged in sequence from bottom to top, characterized in that: The electron transport layer is a SnO2 film with a graphyne passivation layer in situ grown on the surface as described in claim 1.

9. A method for preparing an organic-inorganic halide perovskite solar cell according to claim 8, characterized in that: A SnO2 electron transport layer is formed on the surface of the substrate, and a graphyne passivation layer is formed on the surface of the transport layer in situ according to claim 3; and then a perovskite precursor solution is modified on the surface of the layer by spin coating deposition to obtain a perovskite active layer film; Further, a solution containing phenylethylammonium iodide (PEAI) is spin-coated on the surface of the perovskite active layer film formed above to form a perovskite modification layer on the surface of the perovskite active layer film; after formation, the hole transport layer is modified by spin coating, aged, and a metal counter electrode is prepared after the treatment to obtain a solar cell.

Citation Information

Patent Citations

  • Stannic dioxide / graphdiyne compound interface layer and preparation and application thereof

    CN110817860A

  • Perovskite solar cell taking zirconium oxide passivated tin oxide as electron transport layer and method

    CN111477747A

  • Method for improving performance of perovskite solar cell

    CN115377297A

  • Graphene passivated inorganic perovskite solar cell and preparation method thereof

    CN116404049A

  • CDM interface modification-based perovskite battery and preparation method thereof

    CN117729787A